Evaluating soil carbon and nitrogen dynamics in recently established maize‐soyabean inter‐cropping systems - Oelbermann, M. (2011)
The Pampa comprises the most productive land in Argentina, but the widespread adoption of sole cropping has drastically reduced soil organic carbon (SOC) stocks. This paper presents baseline data on the effects of maizelegume inter-crops compared with maize and soyabean sole crops on SOC and nitrogen (N) stocks, gross SOC turnover, soil microbial biomass (SMB), soil organic matter light fraction (LF) and the partitioning of carbon (C) derived from C3- and C4 crops into SOC, LF and SMB. For soil characteristics, only the C:N ratio was significantly different (0-120 cm) between treatments. Gross SOC and SMB-C turnover time (0-120 cm) was faster in the maize sole crop followed by the inter-crops and the soyabean sole crop. The SMB-C and N were significantly greater in the intercrops. Soil LF-N (0-20 cm) was significantly smaller in the inter-crop. Soil became significantly enriched (0-120 cm) in δ15N in the inter-crop, suggesting that microbial decomposers incorporated C derived from maize and soyabean residues. The greatest proportion of C in the soil and in the soil LF was derived from a C4-C source, and the δ13C of the SMB (0-20 cm) was enriched compared with that of the SOC and the soil LF. Results from this study indicated that after only 1 year of inter-cropping, soil biological and chemical characteristics were influenced positively by this land management practice.